2008
DOI: 10.1200/jco.2008.16.0622
|View full text |Cite
|
Sign up to set email alerts
|

Mature and Immature Extracranial Teratomas in Children: The UK Children's Cancer Study Group Experience

Abstract: Treatment remains primarily surgical, with JEB chemotherapy for YST relapse. No definite response followed JEB for pure MT and IT. Adjuvant chemotherapy after surgery for sacrococcygeal patients is not advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 14 publications
8
135
1
6
Order By: Relevance
“…Long follow-up studies have demonstrated its benign course (Fortt et al, 1969;Robboy et al, 1970). A recent study comparing ovarian immature teratomas with and without GP demonstrated a similar overall good survival but with a higher incidence of early recurrences in the cases associated with GP (Mann et al, 2008;Yoon et al, 2012). Occasionally, GP may precede highly malignant neuroectodermal tumours (Dadmanesh et al, 1997;Shefren et al, 1991;Trabelsi et al, 2002).…”
Section: Clinical Featuresmentioning
confidence: 95%
See 1 more Smart Citation
“…Long follow-up studies have demonstrated its benign course (Fortt et al, 1969;Robboy et al, 1970). A recent study comparing ovarian immature teratomas with and without GP demonstrated a similar overall good survival but with a higher incidence of early recurrences in the cases associated with GP (Mann et al, 2008;Yoon et al, 2012). Occasionally, GP may precede highly malignant neuroectodermal tumours (Dadmanesh et al, 1997;Shefren et al, 1991;Trabelsi et al, 2002).…”
Section: Clinical Featuresmentioning
confidence: 95%
“…GP involvement of lymph nodes (Heifetz et al, 1998;Mann et al, 2008;Muller et al, 2002) is often an incidental finding in abdominal lymphadenectomy specimens, occurring in the marginal sinus (Fig 3B). Secondary associated lesions in GP may include the following:…”
Section: Gliomatosis Peritonei (Gp) (Arrow) Is Present In the Marginamentioning
confidence: 99%
“…Excision of the primary tumour and coccyx should be done in all cases even if a CR has been documented . Recently, Mann et al [14] reported data from the UK Children's Cancer Study group experience. They reported that poor outcome was related to incomplete resection, tunour rupture and higher stage and grade.…”
Section: Discussionmentioning
confidence: 97%
“…According to a series, sacrococcygeal teratomas presented at birth or infancy, ovarian between 5-15 years, testicular before 5 years of age, thoracic tumors occurred throughout infancy and childhood while teratomas at other sites occurred mainly during infancy [5] . Similar results were documented in the present study.…”
Section: Discussionmentioning
confidence: 99%